Comparison of honey and chlorhexidine for oral hygiene and oral health improvement - Adriyani; Retno Setyawati; Moh. Arifin Noor (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Patients admitted to the Intensive Care Unit (ICU) are at high risk of oral health impairment due to decreased levels of consciousness, the use of mechanical ventilation, and limited self-care ability. Poor oral health conditions can serve as a source of microbial colonization and increase the risk of infection, including ventilator-associated pneumonia. Therefore, effective oral hygiene measures constitute an important component of nursing care for critically ill patients. Purpose: To compare the effectiveness of honey and Chlorhexidine in oral hygiene procedures on the oral health status of ICU patients. Method: A quasi-experimental design using a two-group pretest–posttest approach. Sampling was conducted using accidental sampling of ICU patients at Sari Asih Serang Hospital who met the inclusion and exclusion criteria. Oral health status was assessed using the Oral Assessment Guide (OAG) instrument. Data analysis was performed using the Wilcoxon test to assess pre- and post-intervention changes, and the Mann–Whitney test to compare the effectiveness between the two groups. Results: The study findings demonstrated that oral hygiene procedures using both honey and Chlorhexidine significantly improved the oral health status of ICU patients. However, no statistically significant difference was found between the use of honey and Chlorhexidine in improving patients’ oral health status. Conclusion: Honey demonstrates potential as an effective and safe alternative oral hygiene agent for ICU patients. Its use may be considered as part of evidence-based nursing interventions to maintain oral health and prevent infectious complications in critically ill patients.